The pharmacoeconomic efficacy of chemotherapy for malignant neoplasms of the bronchus and lung - S. K. Yarovoy; I. B. Shikina (Фармакоэкономика)
Aim: to conduct a pharmacoeconomic analysis of chemotherapy taking into account the types of malignant neoplasms of the bronchi and lung, and to calculate pharmacoeconomic efficiency.Materials and methods. The materials for the study were the data of the Moscow Cancer Hospital n.a. D.D. Pletnev for 2019. The cost of drugs was calculated according to the data of the website aptekamos.ru (for June 2019).Results and discussion. For 300 patients with squamous non-small cell lung cancer, it is required 3205.5 courses of chemotherapy of I (1747.5) and II (1458) lines. For 200 patients with non-small cell non-squamous EGFR positive lung cancer, it is required 1,413.1 courses of chemotherapy and targeted therapy. For 70 patients with non-squamous cell non-small cell lung cancer with ALK mutation, it is required 450.2 courses of chemotherapy and targeted therapy. For 280 patients with non-squamous cell non-small cell lung cancer lung cancer without mutations, it is required 7515 chemotherapy courses. For 150 patients with small cell lung cancer, it is required 1,656.8 courses of chemotherapy. Thus, a total sample of 1000 patients, excluding the type of malignant neoplasm of broncus and lung are required 14,239.8 chemotherapy courses. The determined cost of 67,000 rubles for the average chemotherapy course per patient takes into account the necessary colony stimulating factors, antiemetic, infusion solutions, etc.; in the case of treatment with erlotinib (the length of the course is 8 months), the cost is 663,408.0 rubles; in the case of treatment with crizotinib (the length of the course is 11 months course), the cost is 2044110.0 rubles. The average cost of drug therapy for one patient with malignant neoplasm of bronchus and lung is 1136155.9 rubles.Conclusion. We determined the pharmacoeconomic dependence of a chemotherapy on the type of malignant neoplasms of bronchus and lung and the main anticancer drug used. The median of the overall survival rate of patients with malignant neoplasms of bronchus and lung was 42 months. The average cost of drug therapy was 27051.3 rubles per month. The median survival rate without therapy is 3 months. Thus, therapy can extend the patient’s life by an average of 39 months. The cost of a month of a saved life is 29132.2 rubles.